Integration of Responsibility and Empathy Character Values in Learning Activities in Elementary Schools - Ayu Wahyuni (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study aims to examine the integration of responsibility and empathy character values in elementary school learning. The research focuses on identifying instructional strategies, classroom practices, and learning approaches that support effective character education, as well as understanding how these values are internalized by students through daily learning experiences. A qualitative approach with a multi-site case study design was employed. Data were collected through in-depth interviews, classroom observations, and document analysis involving principals, teachers, students, and parents selected through purposive sampling. Data analysis followed the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing and verification. The findings indicate that responsibility is developed through structured assignments, classroom routines, and accountability practices, while empathy is fostered through collaborative learning, social interaction, and peer engagement. Teacher role modeling and student-centered learning approaches play significant roles in strengthening the implementation of both character values. School programs and supportive learning environments further enhance the character formation process. However, challenges remain, including limited instructional time, diverse student backgrounds, and inconsistencies in lesson planning and implementation. This study contributes a contextual and integrative framework for embedding responsibility and empathy simultaneously in classroom learning. The findings provide practical implications for educators, school leaders, and policymakers in designing sustainable character education programs that support students’ holistic development and social-emotional competencies.